Penyuluhan Bahaya Narkolema pada Remaja MAS Muhammadiyah Songing - Faridah Faridah; R.Firdaus Wahyudi; Asriadi Asriadi; Rahma Melati Amir; Nurjannah jannah; Rahma rahma (INKAMKU : Integrasi Akademisi dan Masyarakat yang Berkualitas, 2023)
Counseling on the dangers of narcolemma for teenagers of MTS Muhammadiyah Songing aims to provide education and understanding to teeanagers about narcolemma, the dangers it poses and the efforts that can be made to prevent it. Counseling for teenager is important to do because MTS youth in doing school work are often confronted with pornographic content, besides that teenagers also often relieve stress by playing games and reading comics, where these three things are sources of pornographic shows. This is what inspired the writer to do community service by focusing on the subject of service to MTS youth so that they avoid the dangers of narcolemma and can also be an extension of the writer's side in conveying this to the community and youth around the book.